2014
DOI: 10.1007/s13361-014-0916-x
|View full text |Cite|
|
Sign up to set email alerts
|

NanoLC/ESI+ HRMS3 Quantitation of DNA Adducts Induced by 1,3-Butadiene

Abstract: Human exposure to 1,3-butadiene (BD) present in automobile exhaust, cigarette smoke, and forest fires is of great concern because of its potent carcinogenicity. The adverse health effects of BD are mediated by its epoxide metabolites such as 3,4-epoxy-1-butene (EB), which covalently modify genomic DNA to form promutagenic nucleobase adducts. Because of their direct role in cancer, BD-DNA adducts can be used as mechanism-based biomarkers of BD exposure. In the present work, a mass spectrometry-based methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…12,35 We recently reported mass-spectrometry based quantitation of N-7-(1-hydroxy-3-buten-2-yl) guanine (EB-GII) adducts induced by EB (a major genotoxic metabolite of BD) in DNA isolated from peripheral blood leukocytes of smokers, nonsmokers and occupationally exposed BD workers. 19 Although EB-GII was detectable in blood DNA of most human subjects, its concentrations were below the LOQ of the method (0.4 adducts/10 9 nucleotides or 0.2 fmol/150 μg of DNA). N7-guanine adducts such as those induced by BD-derived epoxides are hydrolytically unstable due to the presence of a positive charge on the N7 position of the alkylated base, and are spontaneously released from the DNA backbone over time (Scheme 1).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…12,35 We recently reported mass-spectrometry based quantitation of N-7-(1-hydroxy-3-buten-2-yl) guanine (EB-GII) adducts induced by EB (a major genotoxic metabolite of BD) in DNA isolated from peripheral blood leukocytes of smokers, nonsmokers and occupationally exposed BD workers. 19 Although EB-GII was detectable in blood DNA of most human subjects, its concentrations were below the LOQ of the method (0.4 adducts/10 9 nucleotides or 0.2 fmol/150 μg of DNA). N7-guanine adducts such as those induced by BD-derived epoxides are hydrolytically unstable due to the presence of a positive charge on the N7 position of the alkylated base, and are spontaneously released from the DNA backbone over time (Scheme 1).…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, SPE enriched fractions were subjected to additional enrichment by an offline HPLC method developed in an earlier study. 19 HPLC fractions containing EB-GII and its internal standard were collected, concentrated under vacuum, and reconstituted with 10 μL of water for nanoLC/ESI + -HRMS 3 analysis. HPLC blanks were injected every 10–15 samples to detect any analyte carryover during the offline HPLC clean up procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Aside from proteins and digestion enzymes, ultrafiltration can also remove the partially depurinated DNA backbone from which adducted bases are selectively released following the aforementioned neutral thermal hydrolysis. 182 Despite being simple and rapid, ultrafiltration is always coupled with further clean-up procedures, such as SPE and off-line HPLC because of its relatively low efficiency and specificity in sample purification.…”
Section: Quantitative Analysis Of Dna Adductsmentioning
confidence: 99%
“…Sangaraju et al 182 found that the sensitivity of nLC-nESI-MS/MS was insufficient for the detection of 1,3-butadiene (BD)-DNA adducts in human samples (typical LOD, 0.5 adducts/10 6 nucleosides). To overcome this, the authors developed an nLC-nESI-HRMS 3 method to decrease detection limits to the low fmol to amol range (1–10 per 10 9 nucleosides with 3–76 µg DNA) for their in vivo studies.…”
Section: Quantitative Analysis Of Dna Adductsmentioning
confidence: 99%
“…Sangaraju et al. (, ) employed nanoHPLC‐LIT‐HRMS n for the quantitation of DNA adducts formed with 1,3‐butadiene (BD). BD is a known human carcinogen present in automobile exhaust and cigarette smoke (Lewtas, ).…”
Section: Literature Reviewmentioning
confidence: 99%